Effects of liposomal prostaglandin E1 on periprocedural myocardial injury in patients with unstable angina undergoing an elective percutaneous coronary intervention. Issue 8 (December 2015) - Fan, Yanming; Jiang, Yunfa; Fu, Xianghua; Cai, Junna; Wang, Yanbo; Li, Wei; Gu, Xinshun; Xing, Kun; Bai, Shiru; Bi, Xile
Abstract : Objectives: The aim of this study was to explore whether intravenous administration of liposomal prostaglandin E1 (lipo-PGE1) can reduce the incidence of periprocedural myocardial injury (PMI) in patients with unstable angina undergoing an elective percutaneous coronary intervention (PCI). Patients and methods: In this randomized-controlled study, a total of 219 patients were randomly assigned to a lipo-PGE1 group ( n =110) and a control group ( n =109). Patients in the lipo-PGE1 group received 20 μg/day of lipo-PGE1 diluted in 10 ml of normal saline through an intravenous injection over 5 min starting at 3 days before PCI and continuing for 4 days after PCI. In the control group, 10 ml of normal saline was administered using the same method. The primary end point was the occurrence of PMI defined as an elevation of cardiac troponin I above the upper limit of normal within 24 h after the procedure. The secondary end points were (i) changes in inflammatory factors including plasma high-sensitivity C-reactive protein, tumor necrosis factor α, and interleukin 6 before and at 24 h after PCI; (ii) the incidence of major adverse cardiac events in the patients during hospitalization and 30 days of follow-up after discharge, including cardiac deaths, severe heart failure, malignant arrhythmias, and target vessel revascularization. Results: Within 24 h after PCI, the incidence of PMI was significantly lower in the lipo-PGE1 group compared with that in the control group (20 vs. 36.69%, P =0.009). Although the procedure induced a significant increase in high-sensitivity C-reactive protein, tumor necrosis factor α, and interleukin 6 levels, the values were significantly lower in the lipo-PGE1 group than those in the control group at 24 h after PCI ( P <0.05). The proportion of thrombolysis in myocardial infarction grade 3 in the lipo-PGE1 group was higher than that in the control group (92.72 vs. 82.56%, P =0.037). There were no significant differences between the lipo-PGE1 group and the control group in the incidence of major adverse cardiac events during hospitalization and 30 days of follow-up (2.1 vs. 4%, P =0.72). Multivariate logistic analysis showed that lipo-PGE1 was an independent protective factor against PMI (odds ratio 0.385, 95% confidence interval 0.195–0.760, P =0.006). Conclusion: Intravenous lipo-PGE1 can reduce the incidence of PMI following elective PCI in patients with unstable angina. The benefit of lipo-PGE1 may be associated with the effects of anti-inflammation as well as improvement in coronary microvascular perfusion.